A feasibility study in setting up CF Mini Market in Section 17, Shah Alam / Shariffhudin Mat … [et al.] - Mat, Shariffhudin; Razali, Suhardi; Oyom, Linus; Ismail, Shafre Hassan; Langang, Stephen Karim; Missi, Willybroad; Raja, Julia (1985)
The research that is being undertaken by our group is a feasibility study of setting up of mini-market at Section 17, dhah Alam. The research is undertaken to meat our academic requirements for the completion of Diploma in Business Studies. This research includes the purchasing habits of the deweller, their needs and demand, customer profiles as well as socio-economic data. The research finding revealed that the deweller at dection 17 needed a mini-market urgently as there were no such facilities available there. The writers, therefore strongly recommended based on the finding that a mini-market should be set up as soon as possible.